The Impact of Cinema and Film Screening Places on Improving the Art Cinema Market and Cultural Promotion of Urban Spaces (Case Study: District 6 of Tehran) - Farzin Nematbakhsh Abkenar; Mansoureh Aligholi; Hossein Safarzadeh; Seyed Kamran Nourbakhsh (تحقیقات کاربردی علوم جغرافیایی)
Cinemas and local movie theaters belong to the people of the city, which are designed to have a meaningful presence of citizens in the environment, as well as to strengthen intellectual and social relations. Cinemas and cinema campuses include a valuable collection in terms of culture, old and new art, a place belonging to the people of the city, which is necessary and inevitable in order to spend leisure time of citizens and also to strengthen intellectual and social relations. The purpose of this study is to investigate the impact of cinema and film screening venues on improving the art cinema market and cultural promotion of urban spaces. This research is applied in terms of purpose and descriptive-analytical in terms of method. The statistical population of the study includes the citizens of District 6 of Tehran. The sample size was estimated to be 384 using the Cochran's formula. The library-field method was used to collect data. In order to analyze the research data, structural equation modeling in LISREL software environment was used. The results showed that cinema and movie theaters have a positive and significant effect on the art cinema market and cultural promotion of urban space, so that the variable amount of cinema and movie theaters on the art cinema market more than cultural promotion It was an urban space. Other results of this study also showed that the improvement of the art cinema market has a mediating role in the relationship between cinema and film screening places with the cultural promotion of urban space.